The effect of different retrofitting techniques on the axial load carrying capacity of damaged cylindrical shells. (June 2021) - Rahman Shokrgozar, Hamed; Akrami, Vahid; Jafari Ma'af, Tayebeh; Shahbazi, Naseraldin
Abstract: Load-carrying and deformation capacity of the steel cylindrical shells decreases greatly due to the local damages. This paper investigates the remedial effects of two different retrofitting techniques, namely the application of steel casing and CFRP sheets, on the axial load carrying capacity of damaged cylindrical shells. For this purpose, a series of specimens, including the undamaged, damaged but non-retrofitted, and damaged-retrofitted samples, were tested experimentally and results were compared. Experiments showed that both adopted techniques were capable of improving the load-carrying behavior of damaged specimens. Following the laboratory tests, a numerical study was conducted on the effect of different influencing parameters by focusing on the strengthening technique with steel casing. The main purpose of these analyses was to determine the influence of different parameters and their appropriate value for maximum efficacy. The considered parameters included the diameter to thickness ratio, damage width to wall thickness ratio, damage thickness to wall thickness ratio, casing length to damage width ratio, casing thickness to wall thickness ratio, and damage angle around the circumference. Finally, a practical recommendation was provided on the selection of appropriate parameters for this strengthening technique.